Estratégias utilizadas para a elevação da proficiência de Matemática nas avaliações externas: um estudo de caso na EEM Professor Aloysio Barros Leal - Santos, Maria Jéssyka Almeida dos (2023)
This work seeks to carry out a study based on data about the Mathematics proficiency indexes of the Permanent System of Evaluation of Basic Education of Ceará (SPAECE) and of the System of Evaluation of Basic Education (Saeb), carried out in the 9th grade classes of Elementary School. , 3rd grades of EM and EJA Medium at a state public school in the state of Ceará, namely EEM Professor Aloysio Barros Leal, located in the Barroso neighborhood, in the city of Fortaleza. SPAECE data will be presented referring to the aforementioned classes in the years 2017, 2018, 2019 and 2022 and Saeb in the years 2017, 2019 and 2021, and what strategies were thought and implemented over these years, in the form of training and playful activities and classroom performance assessments such as mini-tests, partial and bimonthly assessments, aimed at increasing these proficiencies. It will also be shown how these strategies influenced in the increase of the students' proficiency indexes in the SPAECE and Saeb evaluations and, consequently, in the elevation of the school's IDEB.